Systematic review and meta-analysis of the incidence and prevalence and 30-year trend of inflammatory bowel diseases in Asia: a study protocol. Issue 11 (19th November 2019) - Safarpour, Ali Reza; Mehrabi, Manoosh; Keshtkar, Abbasali; Edjtehadi, Fardad; Bagheri Lankarani, Kamran
Abstract : Introduction: Inflammatory bowel diseases, including ulcerative colitis (UC), Crohn's disease (CD) and inflammatory bowel disease type unclassified (IBDU), are debilitating conditions that are rapidly growing in developing countries. Given the absence of a comprehensive systematic review and meta-analysis containing a rigorous pooled estimate of incidence and prevalence of UC, CD and IBDU, this study was conducted to determine the incidence and prevalence of these conditions in Asia and their 30-year trend. Methods and analysis: Based on predefined criteria, electronic databases, including PubMed/MEDLINE, Scopus, WoS (Clarivate Analytics), Embase and Google Scholar, and some databases pertaining to Asian countries will be searched for population-based cross-sectional studies and the baseline data and final reports of population-based cohort studies involving paediatric and adult patients, with no language restrictions, from 1 January 1988 to 30 December 2018. Any disagreement in the stages of screening, selecting, quality assessment and data extraction between the two independent reviewers will be resolved by consensus, and if the disagreement is not resolved, a third expert opinion will be sought. The combination method will be used based on methodological similarities in the included studies by the Fixed Effect Model or the Random Effect Model. Forest plots will be plotted for all the studies to show the separated and pooled incidence and prevalence and their corresponding 95% CIs. The Q-statistic test and I 2 statistic will be used to assess statistical heterogeneity. Funnel plots will be used to assess potential reporting bias and nonsignificant study effect. Begg's and Egger's tests will also be performed, and significant results (p>0.1) shall suggest a publication bias, in which case the 'trim and fill' method will be used. The time trends for UC, CD and IBDU will be calculated using a cumulative meta-analysis. Ethics and dissemination: Since this review will use previously published studies, it will not require the consent of an Ethics Committee. The results will be prepared and disseminated through a peer-reviewed journal and will be presented in relevant conferences. PROSPERO registration number: CRD42019131477.